Projeto e implantação de pequena central de geração hidrelétrica: análise de caso - Baldini, José Mateus Guedes [UNESP] (2013)
The objective of this work is to study the implantation feasibility of a small hydropower system in a rural area in Guaratinguetá. Due to its location and accessibility, and the costs involved in extending the public distribution line to the property it could turn become viable the construction of an individual electric generation system. As alternatives, a solar photovoltaic system and combustion engine-electric generator systems were considered. However, the existence of a small river inside the property, the construction of a micro hydropower plant was taken into account. The choice of the micro power hydropower plant was determined by the owner and was based on the costs. The topographic and hydrological profiles as well as the geometrical characteristics of the system, including the civil infrastructure needed and the more adequate turbine, were determined. Finally, the cost spreadsheet was set and the results were compared with those calculated for the extension of the available public distribution system